The effects of cottonseed cake with or without molasses on feed utilization, purine excretion, and milk production of Boran (Bos indicus) cows fed a mixture of wheat and oat straw - Osuji, P.O.; Khalili, H.; Umunna, N.N. (1995)
The effects of 1.35, 1.8, or 2.25 kg dry matter (DM) of cottonseed cake, with (1.85 kg DM) or without molasses, on straw intake, diet digestibility, live-weight change, excretion of purine derivative (PD), and milk production of Boran (Bos indicus) cows were studied. There were no significant (P > 0.05) interactions. Straw intake tended also to decrease from 5.18 to 4.94 kg DM (P < 0.15) with a daily substitution of 107 g kg -1 with increasing levels of cottonseed cake. Molasses increased DM and organic matter (OM: P < 0.01) but decreased crude protein (CP: P < 0.001) and neutral-detergent fibre (NDF: P < 0.01) digestibilities. Molasses (P < 0.05) and increasing levels of cottonseed cake (P < 0.01) in creased daily milk yield from 3.06 to 3.26 and from 2.96 to 3.32 kg, respectively. Molasses increased live-weight by 300 g day - 1 (P < 0.05). Increased levels of cottonseed cake caused a live-weight change of 69g to 467 g day - 1 (P < 0.05). A supply of microbial-N increased (P < 0.01) in molasses diets but microbial-N production kg - 1 digestible OM was not affected by treatments (P > 0.05).